Synthesis and characterization of CNTs/POM nanocomposite acetabular hip cup. Issue 11 (24th July 2018) - Yousef, Samy; Ali, Shady; Abdelnaby, Mohammed Ali; Christova, D.; Hassan, Y.; Samir, D.; Kamel, B.
ABSTRACT: Polyoxymethylene (POM) considered as the most appropriate alternative for ultra-high molecular weight polyethylene (UHMWPE) in the hip joint replacement application due to their biocompatibility, high mechanical properties, and cheapness. The wear is the main cause of the failure in the hip joint and the wear resistance of UHMWPE is still better than the wear resistance of POM. This research aims to improve the wear behavior of POM by blending it with 0.02 wt% of functionalized carbon nanotubes (CNTs) and using paraffin oil dispersion technique to obtain a uniform dispersion. The injection molding and machining process were used to produce the new (CNTs/POM) nanocomposite acetabular hip cup which has a high wear performance. The wear rate of the CNTs/POM cups was evaluated using a total leg joint's simulator at 1, 000 N for 3 million cycles under serum-based lubricated conditions. Moreover, the wear mechanism of cups was examined by scanning electron microscopy as well as the dispersion of CNTs inside the cup matrix. The results show that the wear resistance of POM cup has been improved by adding functionalized CNTs ∼402% and ∼221%, when compared with a virgin POM and UHMWPE, respectively, because of increasing the melting temperature and crystallinity degree. GRAPHICAL ABSTRACT: